Anak Jalanan di Kota Makassar dalam Perspektif Antropologi - Firzah Aurelia; Andi Ima Kesuma; A. Octamaya Tenri Awaru; Abdul Rahman; Najamuddin (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study examines the dynamics of street children's lives in Makassar City through an anthropological approach, highlighting how social and cultural structures influence their identity and behavior. Street children are not only understood as victims of poverty, but they are a social group with their own unique value systems, norms, and internal structures. They form an informal community that demonstrates solidarity, social cohesion, and their own way of life. This study adopts Anthony Giddens' theory of “structuration” and James C. Scott's theory of “resistance” to explain the position of street children as active agents whose daily lives are not only shaped by social structures but also reflexively reproduce and transform these structures through their actions and the power they hold against state dominance, such as symbolic actions and the use of urban space as a arena for negotiating their identities.